Impact of the tetra viral vaccine introduction on varicella morbidity and mortality in the Brazilian macro regions - Marcella Z. Ribeiro; Emil Kupek; Paulo V.Z. Ribeiro; Carlos Eduardo Andrade Pinheiro (Elsevier, 2020)
Objective: To describe the impact of the introduction of the viral tetra vaccine in the National Immunization Program in 2013 for 15-month-old children in mortality rates and hospitalization associated with varicella in Brazil. Methods: Mortality rates and hospitalizations rates associated with varicella were evaluated between 2010 and 2016 and described according to Brazilian macro regions and age. The population was stratified into age groups: < 1 year, 1-4 years, and 5-14 years. Data were collected from the Informatics Department of the Unified Health System. A percentage difference was calculated between rates of hospitalizations and mortality in the pre (2010-2012) and post-vaccination periods (2014-2016) to estimate the approximate effectiveness of the vaccine. Data synthesis: At the national level, vaccination significantly reduced the mortality rates and hospitalizations rates in all age groups analyzed. Among those under 5 years of age, mortality rates and hospitalizations rates decreased 57-49% and 40-47%, respectively. There was a national decrease of up to 57% in the mortality rates due to the disease, with smaller decreases seen in the North and Northeast regions and the largest in the South and Southeast regions. The hospitalizations rates for varicella reached a maximum national decline of 47%. In children aged 1-4 years, with higher vaccination coverage, the highest reduction was observed in both mortality rates and hospitalizations rates, which decreased from 2.6 to 0.4/100,000/year. Conclusions: The tetra vaccine proved to be effective in reducing both mortality and hospitalizations of children and adolescents up to 15 years of age in the 2014-2016 triennium. Resumo: Objetivo: Descrever o impacto da introdução da vacina tetra viral no Programa Nacional de Imunização em 2013 para crianças de 15 meses nas taxas de mortalidade e de internação hospitalar associadas à varicela no Brasil. Métodos: As taxas de mortalidade e de internação hospitalar associadas à varicela foram avaliadas entre 2010 e 2016 e descritas conforme macrorregiões brasileiras e idade. A população foi estratificada em grupos etários: <1 ano; 1-4 e 5-14 anos. Os dados foram coletados do Departamento de Informática do Sistema Unificado de Saúde. Foi realizado um cálculo de diferença percentual entre taxas de internações e mortalidade nos períodos pré (2010-2012) e pós-vacinal (2014-2016) para estimativa de impacto da vacina. Resultados: No nível nacional, a vacinação reduziu significativamente as taxas de mortalidade e de internação hospitalar em todas faixas etárias analisadas. Entre os menores de 5 anos, a taxas de mortalidade e de internação hospitalar diminuíram 57-49% e 40-47%, respectivamente. Houve uma queda nacional de até 57% nos índices de mortalidade pela doença, com menores quedas vistas nas regiões Norte e Nordeste e as maiores nas regiões Sul e Sudeste. As taxas de internação hospitalar por varicela atingiram queda nacional máxima de 47%. Em crianças de 1-4 anos, com maior cobertura vacinal, foi observada a maior redução tanto na taxa de internação hospitalar como na taxa de mortalidade, a qual passou de 2,6 para 0,4/100.000/ano. Conclusões: A vacinação se mostrou efetiva em reduzir tanto mortalidade quanto hospitalizações das crianças e adolescentes de até 15 anos no triênio 2014-2016.